Influence of diverse timescales on the evolution of cooperation in a double-layer lattice - Mao, Yajun; Rong, Zhihai; Xu, Xiongrui; Han, Zhongming (Frontiers in Physics, 2023)
This paper studies the influence of diverse strategy-updating timescales on the evolution of cooperation, defection, and extortion strategies in a double-layer lattice. Individuals can adjust the frequencies with which they updating their strategies adaptively according to their fitness and interlayer information. On the basis of Fermi dynamics, we find that information sharing between the two lattice layers can effectively promote cooperative behavior in a double-layer lattice. In each lattice layer, cooperation-extortion alliances can be formed to defend against invasion by defection. We find that there exists an optimal value of the extortion factor to promote the evolution of cooperation and that the frequency of cooperation in a double-layer lattice is higher than that in a single-layer one.